Predictors of Acute Kidney Injury in Neurocritical Care Patients Receiving Continuous Hypertonic Saline. (January 2017) - Erdman, Michael J.; Riha, Heidi; Bode, Lauren; Chang, Jason J.; Jones, G. Morgan
Background and Purpose: Continuous intravenous 3% hypertonic saline (HTS) infusions are commonly used for the management of cerebral edema following severe neurologic injuries. Despite widespread use, data regarding the incidence and predictors of nephrotoxicity are lacking. The purpose of this study was to describe the incidence and identify predictors of acute kidney injury (AKI) in neurocritical care patients administered continuous infusion HTS. Methods: This was an institutional review board–approved, multicenter, retrospective cohort study of patients receiving HTS infusions at 2 academic medical centers. A univariate analysis and multivariable logistic regression were used to identify predictors of AKI. Data regarding AKI were evaluated during treatment with HTS and up to 24 hours after discontinuation. Results: A total of 329 patients were included in our analysis, with 54 (16%) developing AKI. Those who developed AKI experienced significantly longer stays in the intensive care unit (14.8 vs 11.5 days; P = .006) and higher mortality (48.1% vs 21.9%; P < .001). We identified past medical history of chronic kidney disease (odds ratio [OR]: 9.7, 95% confidence interval [CI]: 1.9-50.6; P = .007), serum sodium greater than 155 mmol/L (OR: 4.1, 95% CI: 2.1-8.0; P < .001), concomitant administration of piperacillin/tazobactam (OR: 3.9, 95% CI: 1.7-9.3; P = .002), male gender (OR: 3.2, 95% CI: 1.5-6.6; P = .002), and African American race (OR: 2.6, 95% CI: 1.3-5.2; P = .007) as independent predictors of AKI. Conclusion: Acute kidney injury is relatively common in patients receiving continuous HTS and may significantly impact clinical outcomes.